KENDALA PENERAPAN INKUIRI DALAM PERKULIAHAN LISTRIK-MAGNET DI LPTK - Suseno, Nyoto (Jurnal Pengajaran MIPA, 2010)
A study about inquiry in electricity and magnetism lecturing was conducted to take a picture inquiry application and its obstacles. Preliminary study had been conducted on four physics education programs of Java and Sumatra island in one or two meeting time, with emphasis aspect to inquiry activity in class through documentation study and observation. Meanwhile the interview just has been done in three data subjects. The data was analyzed qualitatively through: transcription, tabulation, coding, description to see the relationship and the essence of the inquiry based instruction on electricity and magnetism. Research finding showed that lecturers had difficulties in implementating inquiry based instruction on electricity and magnetism lecturing, because electricity and magnetism is abstract concepts. They did not know how to overcome and there is no effort that support inquiry processes in lecturing. The inquiry process could not be observed only in one session, but inquiry process should be conducted continuously during the whole program.